The Effectiveness of Sociodrama Techniques Group Settings to Improve the Prosocial Attitude of SMA Adabiah 2 Padang Students - Ulfa Ulfa; Neviyarni Neviyarni; Indah Sukmawati (Universitas Negeri Padang, 2019)
Facts in the field showed that there are students who have not been able to show prosocial attitudes. Prosocial attitudes need to be showed to strengthen student social relations. The main objective in this study was to reveal the effectiveness of sociodrama techniques in group setting to improve prosocial attitudes of SMA Adabiah 2 Padang students. The research design used was the Pre Experiment model experimental research, with The One Group Pretest-Posttest research design. The subjects of this study were 22 students of XI IPS 5 class. The data collection method used a prosocial attitude scale. Data analysis used Wilcoxon Test and descriptive data analysis. The results of this study indicated that, in general, sociodrama techniques in group setting were effective in improving students' prosocial attitudes. While specifically, there was a significant difference in the average score between the prosocial attitudes of students before and after following the sociodrama activities in group setting.